THE IMPACT OF FINANCIAL ARCHITECTURE ON THE EUROPEAN RETAIL COMPANY PERFORMANCE - V. V. Nazarova; S. P. Glebov (Финансы: теория и практика)
The paper assesses the impact of the financial architecture on the performance of European retail companies. An approach based on a comprehensive analysis of the effects of the financial architecture components is used. The hypotheses are tested using data on public European retailers listed on the London Stock Exchange in 2004 to 2015. To substantiate the interrelationship between the financial architecture and the company performance indicators, the following metrics are analyzed in the paper: the return on assets ratio (ROA) reflecting the ROA in aggregate; the Tobin Q reflecting the investment attractiveness of the company; the strategic performance indicator expressed through the EVA (economic value-added) index reflecting the company’s economic profit (with account for the weighted average cost of capital definition). To simulate the impact of the financial architecture on the company performance, the panel regression method was used making it possible to increase the number of observations, minimize the collinearity between explanatory variables and increase the effectiveness of the estimates obtained. In order to get application insights, two models were constructed: a model with fixed effects taking into account additional characteristics of the company and a model with random effects to minimize the shortcomings of the first model. The analysis shows that the financial architecture of retail companies impacts their strategic performance expressed through the EVA index and performance expressed by the Tobin criterion but has no effect on such performance key figure as ROA. As a result of the research, the performance determinants of large European retailers were identified and a strategic performance model based on the concept of the financial architecture was implemented.